State Level Maize Days - Jat, Mangi Lal; Rana, Dharamvir Singh (2021)
Northwest India has become a major challenge owing to faster depletion of groundwater table, stagnating or declining productivity growth, degrading soil health and environmental quality including air pollution and public health concerns, and diminishing farm profitability. Therefore, diversification of rice crop is the need of hour to sustain the declining natural resources to ensure food security in long-run in Punjab and Haryana. To save earth and to save health, paddy is to be replaced with maize. Currently this coarse grain is cultivated in about 10.2 million ha in India. The increasing interest of the consumers in nutritionally enriched products and rising demand as poultry feed, which accounts 47% of total maize consumption, are the driving forces behind increasing consumption of maize in the country. State Levels Maize Days organized this year in Punjab and Hariyana states of northwest India has gained in stature and popularity on account of the focus on covering very relevant participation from right stakeholders and covering topical issues. The programmes were focused on solutions that will help increase maize productivity by building efficiencies in entire chain and thus generating higher value for the farmers. Scientists and private partners to convince farmers with credible solution to enhance credibility by giving a proof of the technology at the farmers’ field. Timely availability of the input is critical for farmers and providing good market is essential for realisation of diversification with maize replacing rice. In these programmes, knowledge on improved agronomic production technologies and agro-inputs such as seeds of improved maize varieties, herbicides, and pesticides to control fall armyworm have been distributed to the farmers.